МОДУС ВА ДИКТУМ ТУШУНЧАЛАРИ ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
In this article are given definition and analysis of modus, dictum and kensum concepts, which are related to pragmalinguistics. In this article are also observed common and distinctive criteria of modus and modality notions.